Pesticides: Residues in Crops and Their Application. (1st April 2019) - Matthews, Graham
Increasing use of pesticides in China has highlighted that many crops are harvested with residues that affect export of produce. With small farms, farmers have been using very simple knapsack sprayers, but there has been a rapid adoption of using unmanned aerial vehicles (UAV) to spray. More scientific study is now being carried out to reduce operator exposure and residues in crops. There has undoubtedly been a vast change in the global use of pesticides. This is particularly evident in China, which has in recent years become a major producer of pesticides and exporter of actives for use elsewhere. Needing to support over 20% of the world population, but having only 10% of the arable land, it has needed to use pesticides to improve its own agricultural production. Within China, pesticide use has increased to about 1.8 million tons of pesticides in 2016, making China the world?s largest pesticide user. These are applied through manually operated knapsack sprayers of basically one design and manufactured in China, as farms are quite small. More recently the use of small drones (Unmanned aerial vehicles (UAV) has expanded rapidly to avoid walking through crops, such as rice, although the equipment currently used needs further development. With concern about residues in crops Liu and Guo examined the regulations around the world that impact on pesticide residues. Legislation concerning residues has been developed mostly within the European Union, USA and Japan, whereas the developing countries have lacked the resources and expertise to implement and enforce legislation adequately. In general, the Maximum Residue Level (MRL) is defined as the upper legal level for pesticide residues (expressed in mg/kg) in or on food or feed, based on Good Agricultural Practices (GAP), including observance of a preharvest interval (PHI), to ensure the lowest possible consumer exposure. In China, the Food Safety Law was implemented only in 2009 and coupled with a series of other announcements and programs issued by the Ministry of Agriculture, aimed at reducing pesticide residues. At present far fewer MRLs have been established in comparison with the EU and there is a lack of systematic detection methods throughout China. Harmonisation of the MRLs has been an important issue with produce being exported, so China now has to improve the scientific risk assessment of MRLs.